Identification of structural and soil properties from vibration tests of the Hualien containment model. - Luco, J. Enrique (Earthquake engineering & structural dynamics.)
Measurements of the response of the one fourth scale reinforced concrete Hualien (Taiwan) containment model obtained during forced vibration tests are used to identify some of the characteristics of the super-structure and the soil. In particular, attempts are made to determine the fixed-base modal frequencies, modal damping ratios, modal masses and participation factors associated with translation and rocking of the base. The shell superstructure appears to be softer than could have been predicted on the basis of the given geometry and of test data for the properties of concrete. Estimates of the shear wave velocity and damping ratio in the top layer of soil are obtained by matching the observed and theoretical system frequency and peak amplitude of the response at the top of the structure. The resulting models for the superstructure and the soil lead to theoretical results for the displacement and rotations at the base and top of the structure which closely match the observed response.